(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2012)
The Information Technology Infrastructure Library (ITIL) provides a framework of best practices for managing of the information technology (IT) services. In the framework of this study it is clear that it does not have space in your body for information architecture. One of the goals information architecture to organize information for decision making, how can this be out of context? The proposed positioning of this paper presents evidence that the perception that the concepts of information architecture are present on the needs of IT service management. This proposal will encourage the union of bodies of knowledge thereby facilitating the creation of strategy and design services. Keywords: Information Architecture. Services Management. TI Services Infrastructure. Link para o texto completo (PDF) http://www2.marilia.unesp.br/revistas/index.php/bjis/article/viewFile/505/1474